1998
DOI: 10.1109/8.662655
|View full text |Cite
|
Sign up to set email alerts
|

Time-domain sensing of targets buried under a rough air-ground interface

Abstract: Abstract-We consider plane wave time-domain scattering from a fixed target in the presence of a rough (random) surface with application to ground penetrating radar. The timedomain scattering data are computed via a two-dimensional (2-D) finite-difference time-domain (FDTD) algorithm. In addition to examining the statistics of the time-domain fields scattered from such a surface, we investigate subsurface target detection by employing a (commonly used) matched-filter detector. The results of such a detector are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 36 publications
0
47
0
Order By: Relevance
“…Since we are concerned with the numerical analysis of rough-surface scattering, this does not present an obstacle in our study. The exponential correlation functions has the form (2) Analogous to the Gaussian case, the parameter represents the correlation length. Authors have proposed other models, constituting hybrids of the Gaussian and exponential functions, characterized by two or more correlation-length-type parameters, taking into account the roughness at different scales.…”
Section: A Traditional Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since we are concerned with the numerical analysis of rough-surface scattering, this does not present an obstacle in our study. The exponential correlation functions has the form (2) Analogous to the Gaussian case, the parameter represents the correlation length. Authors have proposed other models, constituting hybrids of the Gaussian and exponential functions, characterized by two or more correlation-length-type parameters, taking into account the roughness at different scales.…”
Section: A Traditional Modelsmentioning
confidence: 99%
“…The statistical analysis of time-domain electromagnetic scattering from a rough surface has been investigated previously [2], [3]. However, the vast majority of work on rough-surface scattering has been addressed in the frequency domain [4]- [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, we caution that this does not imply that V polarization in the vicinity of the Brewster angle is always better than H polarization. In addition to increasing the RCS of the target it has been demonstrated that V polarization also can yield enhanced backscatter from surface roughness [Dogaru and Carin, 1998], vis-h-vis H polarization. Hence for incidence near the Brewster angle in the vicinity of a rough surface the gain in target signature amplitude is balanced by a commensurate increase in the roughness-induced clutter [Dogaru and Carin, 1998].…”
Section: Bor Scattering: Half-space Casementioning
confidence: 99%
“…This again must be treated with caution. While the target signature is reduced with increasing 0, so often is the signature of roughness-induced clutter, and it is the balance between the target and clutter signature strengths that ultimately impacts detection and classification performance [Dogaru and Carin, 1998]. …”
Section: Bor Scattering: Half-space Casementioning
confidence: 99%
“…Some works have explored numerical solutions [3][4][5], but have concentrated primarily on two dimensional scattering problems to reduce computational complexity. The two dimensional rough surface ground (i.e., three dimensional (3D) scattering problem) is a more realistic problem as investigated by mangy researchers [6][7][8]. In [8], the EM scattering from a 3D shallow object buried under a 2D random rough dielectric surface is analyzed by using the steepest descent fast multi-pole method.…”
Section: Introductionmentioning
confidence: 99%